Requirements and standards facilitating quality improvement for reporting systems in gastrointestinal endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Bretthauer, Michael; Aabakken, Lars; Dekker, Evelien; Kaminski, Michal F.; Rösch, Thomas; Hultcrantz, Rolf; Suchanek, Stepan; Jover, Rodrigo; Kuipers, Ernst J.; Bisschops, Raf; Spada, Cristiano; Valori, Roland; Domagk, Dirk; Rees, Colin; Rutter, Matthew D.; on behalf of the ESGE Quality Improvement Committee (Endoscopy, 2016)
To develop standards for high quality in gastrointestinal (GI) endoscopy, the European Society of Gastrointestinal Endoscopy (ESGE) has established the ESGE Quality Improvement Committee. A prerequisite for quality assurance and improvement for all GI endoscopy procedures is state-of-the-art integrated digital reporting systems for standardized documentation of the procedures. The current paper describes the ESGE’s viewpoints on the requirements for high-quality endoscopy reporting systems in GI endoscopy. Recommendations1 Endoscopy reporting systems must be electronic.2 Endoscopy reporting systems should be integrated into hospitals’ patient record systems.3 Endoscopy reporting systems should include patient identifiers to facilitate data linkage to other data sources. 4 Endoscopy reporting systems shall restrict the use of free-text entry to a minimum, and be based mainly on structured data entry. 5 Separate entry of data for quality or research purposes is discouraged. Automatic data transfer for quality and research purposes must be facilitated.6 Double entry of data by the endoscopist or associate personnel is discouraged. Available data from outside sources (administrative or medical) must be made available automatically. 7 Endoscopy reporting systems shall facilitate the inclusion of information on histopathology of detected lesions, patient satisfaction, adverse events, and surveillance recommendations.8 Endoscopy reporting systems must facilitate easy data retrieval at any time in a universally compatible format.9 Endoscopy reporting systems must include data fields for key performance indicators as defined by quality improvement committees.10 Endoscopy reporting systems must facilitate changes in indicators and data entry fields as required by professional organizations.